Asymptotic Stability of Fractional Stochastic Neutral Differential Equations with Infinite Delays - R. Sakthivel; P. Revathi; N. I. Mahmudov (Abstract and Applied Analysis)
We study the existence and asymptotic stability in pth moment of a mild solution to a class of nonlinear fractional neutral stochastic differential equations with infinite delays in Hilbert spaces. A set of novel sufficient conditions are derived with the help of semigroup theory and fixed point technique for achieving the required result. The uniqueness of the solution of the considered problem is also studied under suitable conditions. Finally, an example is given to illustrate the obtained theory.